Centro de investigación y jardín botánico, barrio Las Acacias - Tamayo Santana, Karla Rosalyn (2018)
The topic Investigation Center Botanical Garden, corresponds to the process of equipment development implemented in the urban proposal Eje de la 10 de Agosto. The Urban Proposal previously made by the workshop ARO - 960, was based on four phases: the first one is the research and diagnosis of the basic urban spatial structure based upon the research field. Development of the urban concept proposal. Establishment of an urban spatial proposal and proposal of a preliminary design of urban and architectural projects. The Acacias district is a site without features defined, but is located next to a large green space, the Bicentennial Park, also the 10 August and its continuation Galo Plaza Lasso has certain problematic characteristics such as the lack of areas Greens that provide environmentally to the city. Finally, the thesis topic seeks to implement an equipment which is seam between the Park and the city, and on the basis of its functionality environmentally contribution to the city, with the study, production and promotion of the species endemic to the Metropolitan district of Quito.